Virtual Environment as a Tool for Increasing Students' Natural Science Literacy - Abeldina, Zhaidary; Makysh, Gulmira; Moldumarova, Zhibek; Abeldina, Rauza; Moldum, Zhuldyz (International Journal of Engineering and Technology, 2018)
The article is devoted to the quality of natural science education at universities. Moreover, this article reveals the causes and consequences of the decline in the level of mastery of these disciplines. The modernization of education efficiency aimed at improving the quality and accessibility of education itself largely depends on the way of using the objective information. This information can be received in the framework of studies of various types of education results such as monitoring studies of the republican level and international comparative studies. All these studies provide the information on the state of education; they allow correlating the planned and achieved results and based on that identifying the most significant education problems that need to be solved. The monitoring of the education quality implies the development of criteria for the assessments of knowledge for any stage of education. The calculation of students' progress rating can be one of the approaches to this problem. The assessment of the output knowledge of the students' progress rating can be done by using the electronic journal, which is the part of a university's automated information system. The standardization of the final rating on a scale of 0 to 100 creates an optimal opportunity to compare the results of educational progress at all stages of training. The use of virtual tools and software products is one of the essential interactive elements of the e-learning course in the virtual educational environment, which is particularly important in the study of natural sciences. These tools combine methodological and pedagogical technologies, information resources and modern software and help to monitor the educational process and find the solution to the issues of its quality.
Keywords: monitoring of the educational process; students' progress rating; virtual educational space; electronic journal.